Perubahan Sosial Budaya Melayu: Marginalisasi ke Generasi (Studi Etnografi di Desa Tanjung Pasir Labuhanbatu Utara) - Mona Ratu Munthe; Ratih Baiduri; Puspitawati Puspitawati (Universitas Islam Negeri (UIN) Salatiga, 2026)
This study aims to delineate the regeneration process of Malay culture, identify the mechanisms of marginalization within community social life, and analyze the challenges and opportunities in preserving Malay culture. This research employs an ethnographic method as its primary approach, which includes participant observation and in-depth interviews with community leaders, as well as the younger generation in the village. Through this approach, it is expected to provide a comprehensive understanding of the socio-cultural shifts in Malay culture from marginalization to regeneration. This study utilizes Antonio Gramsci's Theory of Cultural Hegemony as its foundational framework for analysis. The findings indicate that the regeneration process of Malay culture in Tanjung Pasir Village is progressing negatively and experiencing a complete disruption in the cultural transmission chain; furthermore, the mechanisms of Malay culture operate simultaneously through genetic transmission (family) and communal ritual expressions (customary feasts). However, regarding the challenges and opportunities of cultural preservation, the local community and artisans can filter the adverse effects of globalization while leveraging technology as a tool (opportunity) to repackage Malay culture, making it appealing once again to the younger generation. This research is expected to serve as a reference for relevant stakeholders in developing programs that support cultural regeneration, as well as enhancing public awareness of the importance of maintaining cultural identity amidst the waves of change.